IrO2-ZnO Hybrid Nanoparticles as Highly Efficient Trifunctional Electrocatalysts - Kwak, Inhye; Kwon, Ik Seon; Kim, Jundong; Park, Kidong; Ahn, Jae-Pyoung; Yoo, Seung Jo; Kim, Jin-Gyu; Park, Jeunghee (American Chemical Society, 2017)
Development of high-performance catalysts is very crucial for the commercialization of sustainable energy conversion technologies. Searching for stable, highly active, and low-cost multifunctional catalysts has become a critical issue. In this study, we report the synthesis of IrO2-ZnO hybrid nanoparticles and their highly efficient electrocatalytic. activities toward oxygen/hydrogen evolution reaction (OER/HER) as well as oxygen reduction reaction (ORR). For comparison, we synthesized RuO2-ZnO, showing a smaller catalytic activity than IrO2-ZnO, which provides robust evidence for the unique synergic effect of these hybrid structures. IrO2-ZnO and RuO2-ZnO exhibit excellent OER catalytic performance with Tafel slopes of 57 and 59 mV decade(-1), respectively. For HER, IrO2-ZnO shows a higher catalytic activity than RuO2-ZnO. The numbers of electrons involved in the ORR were 3,7 and 2.8, respectively, for IrO2-ZnO and RuO2-ZnO. The remarkable catalytic performance of IrO2-ZnO would be ascribed to the abundant oxygen vacancies and the metallic states of Ir, which ensure excellent catalytic activity and stability.
Keywords: OXYGEN EVOLUTION REACTION; BIFUNCTIONAL ELECTROCATALYST; REDUCTION REACTION; CARBON; CATALYSTS; OXIDES; IR; DESIGN; RU